Malignant Hypertension: Ocular Manifestations. (2006) - Muñoz, Silvia; Martín, Nieves; Arruga, Jorge
Abstract : Malignant hypertension may be the first manifestation of systemic hypertension. We report a clinical case of a Caucasian 41-year-old man with no previous history of blood hypertension seen at casualty because of blurred vision. Fundus examination disclosed optic disk swelling, retinal hemorrhages and infarcts. The blood pressure was 220/130 mmHg. After the appropriate management of hypertension, optic disk and retinal edema resolved, leaving minor changes as mild optic disk pallor and hard exudates.